Preparedness and perception of pandemics among medical students - Sawhney, Divya; Goel, N. K.; Prashar, Savita; Rana, Kirtan (International Journal Of Community Medicine And Public Health, 2023)
Background: Infectious diseases continue to pose a serious threat to public health as pandemic or epidemic. Good knowledge about the emerging diseases and perception about the severity of disease is important to control these situations. The current study was undertaken to assess the preparedness of medical students in terms of level of knowledge, perception and willingness to volunteer during pandemics. Methods: A cross-sectional study was conducted among 400 medical students using simple random sampling method. A self-structured and validated questionnaire was used to collect data which was then analyzed using frequencies, mean, t-test, Chi square test and ANOVA. Results: The overall knowledge scores among majority (59.8%) students belonged to ‘very good’ category while 7.5% obtained ‘unsatisfactory’ scores. Mean scores for knowledge were significantly different in different stratified groups. One third participants were stressful during earlier pandemic. 68.5% strongly stated that being healthy and prior vaccination were important factor for preparedness and willingness to volunteer. Besides personal protective equipment (PPE), separate accommodation and transportation for volunteering duration and psychological support are other crucial factors. Conclusions: Majority of the students in the study displayed adequate preparedness in terms of knowledge, awareness and willingness during the recent pandemics. However, the level of risk perception was evident. By imparting good knowledge and prior training about the pandemic, preventive strategies, tackling stress and identifying and addressing other relevant issues, medical college students can prove to be an asset for facing a pandemic like situation in our country.